The influence of patriarchal culture on social life in Javanese families in Wolio sub-district - Korniawati, Dian; Rahim, Abdul (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This study analyzes the influence of patriarchal culture on the social life of Javanese families in Wolio Sub-district. Patriarchal culture is a concept that refers to men exercising ownership and control in the family. The influence of patriarchal culture on Javanese families in Wolio Sub-district was studied using qualitative methods including data collection through primary data collection and data analysis. The purpose of this study is to reveal the influence of patriarchal culture on the social life of Javanese families in Wolio Sub-district. The results of this paper are expected to provide information for stakeholders responsible for developing programs and activities aimed at reducing the negative impact of patriarchal culture on Javanese families in Wolio Sub-district. This research uses the patriarchal culture theory developed by Wax Weber, which is a cultural theory that explains the concept of patriarchal culture. This theory can be used to better analyze the influence of patriarchal culture on the social life of Javanese families in Wolio Sub-district. This research uses a qualitative methodology that utilizes data collection through primary data collection and data analysis. Data collection is done through in-depth interview methods conducted to family members in the Wolio area. The data obtained will be analyzed using patriarchal cultural theory. This research is expected to provide information for responsible stakeholders in developing programs and activities aimed at reducing the negative impact of patriarchal culture on Javanese families in Wolio District.